2016
DOI: 10.1186/s13256-016-1107-0
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous cerebrospinal fluid leak of the sphenoid sinus mimicking allergic rhinitis, and managed successfully by a ventriculoperitoneal shunt: a case report

Abstract: BackgroundSpontaneous cerebrospinal fluid leaks are rare but may lead to confusion with other diseases in patients without history of trauma. We report a rare case unusual for two reasons. First, our patient was put under antiallergic medication for months before the diagnosis of spontaneous cerebrospinal fluid leak of the sphenoid sinus. Second, our patient was managed successfully by a ventriculoperitoneal shunt.Case presentationOur patient was a nonobese 49-year-old Arab man without history of trauma or sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 19 publications
0
12
0
2
Order By: Relevance
“…However, CSF rhinorrhea occurred again after lumbar drainage, probably because of the persistently high ICP. It was already reported that a patient with spontaneous CSF rhinorrhea was managed successfully by a VPS alone (Darouassi et al, 2016). Even if the endoscopic repair for the present case had not been carried out yet, placement of a permanent CSF drain, in the form of a VPS or LPS, could be considered in this case.…”
Section: Discussionmentioning
confidence: 85%
“…However, CSF rhinorrhea occurred again after lumbar drainage, probably because of the persistently high ICP. It was already reported that a patient with spontaneous CSF rhinorrhea was managed successfully by a VPS alone (Darouassi et al, 2016). Even if the endoscopic repair for the present case had not been carried out yet, placement of a permanent CSF drain, in the form of a VPS or LPS, could be considered in this case.…”
Section: Discussionmentioning
confidence: 85%
“…Indeed, assuming that most spontaneous skull base CSF leak patients have underlying IIH, and that a CSF leak is a sign of chronic poorly controlled IIH, 35 one might hypothesize that the leak acts as a “pressure release valve,” providing relief of symptoms and signs of raised ICP, precluding or delaying the presentation of IIH. 22 Papilledema has been uncommonly reported at presentation in CSF leak patients, with a pooled prevalence of only approximately 5%, 3 , 6 , 2326 but preoperative signs suggestive of raised ICP were underestimated in these studies, as these also include sixth nerve palsy and peripapillary changes of resolved papilledema. None of the previous studies provided details regarding a previous history of IIH or the presence of resolved signs of intracranial hypertension.…”
Section: Discussionmentioning
confidence: 89%
“…[ 4 , 15 ] Constipation is reported in more than half of the patients with PAF and is frequently an early symptom of the disease. [ 5 ] The repetitive closed glottis efforts following chronic constipation leads to sustained intra-abdominal and intra-thoracic increased pressure and could predispose to an intermittent or permanent ICH with weakness of the dura mater and CSF leaks.…”
Section: Discussionmentioning
confidence: 99%